Pendampingan Penerapan Model Latihan Small Side Games Sekolah Sepak Bola (SSB) di Kecamatan Percut Sei Tuan Kabupaten Deli Serdang - Hasibuan, Nurman; Nusri, Ardi; Gultom, Syamsul; Raswin, Raswin; Ratno, Puji; Azandi, Filli (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2025)
The purpose of this activity is to assist partner soccer schools (SSB) in addressing various issues, particularly those related to coaching resources, training equipment, and organizational management, with the ultimate goal of establishing an independent and professional soccer academy. The objectives of this activity include developing qualified soccer coaches, implementing the Small Sided Games (SSG) training method, and providing standardized training facilities. The methods used include conducting coaching clinics for coaches and prospective coaches, training in developing effective SSG-based training programs, and providing adequate training facilities. The results of this activity indicate that four coaches have been trained who are able to implement the SSG training model, the SSG method has been integrated into routine training sessions, and the availability of training facilities that meet early childhood training standards. In addition, the implementation of the SSG method has been proven to significantly improve students' aerobic endurance, as evidenced by the increase in VO2 Max values in the fitness test results of SSB Sinar Pagi students.